Legal Politics of Changes to Marriage Laws in Indonesia - Hanafi, Syawaluddin (Hukum Keluarga Islam IAIN LANGSA, 2024)
The research aims to analyze changes to articles in Law Number 16 of 2019 concerning Marriage which are the result of revisions to previous provisions, namely Law Number 1 of 1974 concerning Marriage. This research is a juridical research by analyzing legal politics regarding changes in marriage law using a statutory approach, case approach, conceptual approach, and legal comparative approach. The results of this research are: First, the revision carried out by the government still leaves legal problems, this is based on the decision of the Constitutional Court in several judicial reviews of Law no. 1 of 1974 concerning Marriage. Second, the age limit regulated in Law no. 16 of 2019 concerning Marriage is not yet ideal and synergistic with other statutory provisions. Third, the purpose of the amendment to Law no. 1 of 1974 concerning Marriage is to reduce legal problems in society. On the other hand, the same problems still occurred when the previous provisions were implemented, such as the death rate for girls who married at a young age, the increasing number of requests for marriage dispensations, and the failure to achieve the marriages desired by law. However, changes to the marriage age limit provisions at least attempt to minimize cases of early child marriage in Indonesia.